Multiomic analysis of a dried single-drop plasma sample using an integrated mass spectrometry approach. Issue 20 (12th August 2020) - Gao, Weina; Zhang, Qiaoyun; Su, Yiran; Huang, Peiwu; Lu, Xue; Gong, Qinyue; Chen, Wendong; Xu, Ruilian; Tian, Ruijun
Abstract : An easy-to-use and fast approach was developed for integrated proteomic and metabolic profiling in a dried single-drop plasma sample. Abstract : An easy-to-use and fast approach was developed for integrated proteomic and metabolic profiling in a dried single-drop plasma sample. Plasma collection, room temperature storage, and sample preparation for both proteins and metabolites were seamlessly integrated in one spintip device. MS-based multiomic profiling using the same nano LC-MS system identified more than 150 proteins and 160 metabolites from the 1 μL plasma sample in 6 hours. Further combination with micro-flow LC and targeted MS made it a promising approach for the fast profiling of molecular biomarkers with high sensitivity and accuracy.